Pelatihan Afirmasi Positif Terhadap Kepercayaan Diri Disabilitas Psikososial di Sehati Sukoharjo - Sindi Berliana Rahmawati; Aidila Sabila Putri; Angga Eka Yuda Wibawa; Uswatun Marhamah; Anni Nurul Hidayati (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The large number of people with psychosocial disabilities, especially in Central Java Province, shows the importance of effective interventions to support the recovery process. One promising approach is positive affirmation training, which is designed to help individuals develop a more optimistic mindset and build self-confidence. Low self-confidence is often an obstacle for people with psychosocial disabilities to actively participate in society, so an approach that can overcome these obstacles is needed. The purpose of this community service is to teach positive affirmation techniques to members of the ODDP Sehati organization to be implemented in everyday life to support the self-confidence of psychosocial disabilities. The method used is a direct training method for members of the ODDP Sehati Sukoharjo organization. The results obtained after this training showed that intervention through positive affirmation training helped participants to be more self-accepting, reduce self-stigma, and strengthen positive views of personal abilities. This supports the importance of positive affirmation training as part of a psychosocial rehabilitation approach, because it can help individuals with psychosocial disabilities to be more confident and able to function optimally in everyday life.